1466 Closed Incision Negative Pressure Wound Therapy reduces Surgical Site Infection following Emergency Laparotomy: A Propensity Matched NELA Registry Study. (12th October 2021) - Blyth, U; Chung, J N C; Ali, O; Hawthornthwaite, E; Watkinson, T; Harji, D; Griffiths, B
Abstract: Background: Surgical site infection (SSI) contributes to a significant proportion of post-operative morbidity in people undergoing emergency surgery. Prophylactic closed incision negative pressure therapy (CINPT) has been shown to reduce SSI rates in patients undergoing elective laparotomy however there is limited evidence for their use in the emergency setting. This study aimed to determine whether prophylactic CINPT provides comparable SSI rate to SSD for midline incision following emergency laparotomy. Method: A registry-based, prospective cohort study was undertaken using data from National Emergency Laparotomy Audit (NELA) database at our centre. The primary outcome measure was SSI as defined by the Centers for Disease Control (CDC) criteria. Secondary outcomes included 30-day post-operative morbidity and grade using Clavien-Dindo (CD) classification and the Comprehensive Complication Index, length of stay, 30-day mortality and readmission rates. CINPT and standard surgical dressing group were compared with respect to peri-operative characteristics and post-operative outcomes. A propensity- score matching (PSM) was performed to mitigate for selection bias. Results: A total of 1484 patients were identified. Following PSM, a matched cohort of 474 patients were identified with 237 patients in each arm. SSI rate in CINPT cohort was found to be significantly lower compared to the SSD cohort (16.9% vs. 33.8%, p < 0.001). The rate of superficial and deep infections was higher in the standard dressing arm compared to the CINPWT, p < 0.001. There were no overall differences in 30-day morbidity and grade of post-operative complications. Conclusions: Prophylactic CINPT in the emergency laparotomy is associated with reduced SSI rates.